The Theory of Quark and Gluon Interactions - Yndurain, Francisco J. (Theoretical and Mathematical Physics,, 2006)
F. J. Ynduráin's book on Quantum Chromodynamics has become a classic among advanced textbooks. First published in 1983, and translated into Russian in 1986, it now sees its fourth edition. It addresses readers with basic knowledge of field theory and particle phenomenology. The author presents the basic facts of quark and gluon physics in pedagogical form. Theory is always confronted with experimental findings. The reader will learn enough to be able to follow modern research articles. This fourth edition presents a new section on heavy quark effective theories, more material on lattice QCD and on chiral perturbation theory.